Impact of Technological Innovation on Productivity and Competitiveness of the Culinary Industry - Ramdhan Kurniawan; Andi Naila Quin Azisah Alisyahbana; Soussou Raharimalala; Maria Reski; Enzel D. S. Situmorang; Nurul Fadilla (Indonesian Journal of Business and Entrepreneurship Research, 2024)
This study analyzes the impact of technological innovation on productivity and competitiveness within the bread industry, focusing on a case study of Usaha Roti Gembong Gembul in Makassar. A descriptive qualitative approach was employed, using data collected through in-depth interviews, direct observations, and relevant document analysis. The research provides a comprehensive examination of how new technologies are integrated into various operational aspects, including production processes, inventory management, and marketing strategies. The findings offer practical insights for industry players, highlighting the importance of adopting and utilizing technology to enhance operational efficiency and competitiveness. Respondents generally expressed positive perceptions regarding the availability, accessibility, and efficiency of the technology implemented. Furthermore, high levels of satisfaction were noted concerning product quality and decision-making processes, especially in managing risks and uncertainties. These findings underscore the critical role of technological innovation in boosting both productivity and competitiveness in the bread industry.